2023
DOI: 10.1037/tra0001369
|View full text |Cite
|
Sign up to set email alerts
|

The role of PTSD symptom severity and relationship functioning in male and female veterans’ mental health service use.

Abstract: Objective: Previous research has shown that difficulties in intimate relationships promote mental health treatment seeking for male veterans, but findings for female veterans have been mixed. The current study sought to further evaluate whether intimate relationship functioning is a motivator for mental health treatment seeking for male and female veterans and examine the impact of different types of trauma exposure on this association. Method: Using data from a longitudinal study, we examined whether intimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition, gender may influence treatment-seeking behavior among veterans. A longitudinal study conducted by Harper et al aimed to provide clarity on the associations between PTSD, intimate relationship functioning, and mental health service use for male and female veterans [ 14 ]. The findings revealed that poorer intimate relationship functioning related to PTSD severity had a positive effect on male veterans, but not women, in seeking treatment for PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, gender may influence treatment-seeking behavior among veterans. A longitudinal study conducted by Harper et al aimed to provide clarity on the associations between PTSD, intimate relationship functioning, and mental health service use for male and female veterans [ 14 ]. The findings revealed that poorer intimate relationship functioning related to PTSD severity had a positive effect on male veterans, but not women, in seeking treatment for PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that poorer intimate relationship functioning related to PTSD severity had a positive effect on male veterans, but not women, in seeking treatment for PTSD. However, women veterans in general were more likely to seek treatment than men [ 14 ]. Moreover, appropriate peer support significantly impacts PTSD symptoms, aiding veterans in better managing them [ 54 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations